Asymmetric Information and Adverse Selection in Mauritian Slave Auctions - DIONNE, GEORGES; ST-AMOUR, PASCAL; VENCATACHELLUM, DÉSIRÉ (Review of Economic Studies, 2009)
Information asymmetry is a necessary prerequisite for testing adverse selection. This paper applies this sequence of tests to Mauritian slave auctions. The theory of dynamic auctions with private and common values suggests that when an informed participant is known to be active, uninformed bidders will be more aggressive and the selling price will be higher. We conjecture that observable family links between buyer and seller entailed superior information and find a strong price premium when a related buyer purchased a slave, indicative of information asymmetry. We then test for adverse selection using sale motivation. Our results indicate large discounts on voluntary as compared to involuntary sales. Consistent with adverse selection, the market anticipated that predominantly low-productivity slaves would be brought to the market in voluntary sales.